Bhūpendranātha Jaina abhinandana grantha - Jaina, Sāgaramala.; Jaina, Bhūpendranātha; Pārśvanātha Vidyāpīṭha. (Bhupendra Nath Jain felicitation volume, 1998)
Includes bibliographical references.
Includes bibliographical references.
Festschrift in honor of Bhūpendranātha Jaina, b. 1918; contributed research papers chiefly on Jainism and Jaina philosophy.
In Hindi; some articles in English; includes passages in Prakrit and Sanskrit.
Keywords: Jaina philosophy. / http://id.loc.gov/authorities/subjects/sh85100942; Jainism. / http://id.loc.gov/authorities/subjects/sh85069282